Latissimus Dorsi Muscle Flap with a Distally Based Serratus Anterior Extension for Salvaging Aortic Graft Infection. Issue 6 (June 2020) - Tsuge, Itaru; Saito, Susumu; Yamazaki, Kazuhiro; Sakamoto, Kazuhisa; Tsunoda, Shigeru; Katsube, Motoki; Arata, Jun; Sakamoto, Michiharu; Minatoya, Kenji; Morimoto, Naoki
Abstract : Supplemental Digital Content is available in the text.